Sistem Informasi Distribusi Bantuan Ternak untuk Pengelolaan dan Penyaluran - Nanda, Katya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2021)
The Livestock Aid Distribution Information System is designed to streamline the management and distribution of livestock aid. This system provides a user-friendly interface for beneficiaries to apply for aid, track the status of their applications, and receive updates. It also enables administrators to efficiently review applications, verify eligibility, and manage the distribution process. By integrating features such as automated eligibility checks, real-time tracking of distribution status, and detailed records of beneficiaries, the system enhances transparency and operational efficiency. Additionally, the system includes tools for reporting and analytics, allowing management to make data-driven decisions and optimize the distribution process. The system supports integration with various logistical platforms, ensuring secure and timely delivery of livestock aid. Overall, the Livestock Aid Distribution Information System aims to improve the management and effectiveness of livestock aid programs, ensuring that assistance reaches eligible beneficiaries promptly and effectively.